Plant growth promoting activity of Bacillus pumilus in tea (Camellia sinensis) and its biocontrol potential against Poria hypobrunnea - and P. ROYCHOWDHURY, U. CHAKRABORTY*, B.N. CHAKRABORTY (Indian Phytopathology, 2013)
Bacillus pumilus TRS-3, isolated from tea rhizosphere, was evaluated for its plant growth promoting and biocontrol activities both in vitro and in vivo. The bacterium showed positive PGPR traits in vitro such as phosphate solubilization, siderophore production, volatile production and IAA secretion. B. pumilus inhibited growth of tea root fungal pathogens such as Poria hypobrunnea, Fomes lamaoensis, Sphaerostilbe repens, Scleorotinia sclerotiorum, and Sclerotium rolfsii. Both heat sterilized and cold sterilized cell free culture filtrate of the bacterium inhibited the growth of P. hypobrunnea causing root rot and stem canker of tea. Partitioning of the culture filtrate with six different solvents-benzene, hexane, chloroform, diethylether, petroleum ether and ethylacetate followed by their bioassay against the pathogens revealed diethyl ether fraction to be most inhibitory though other fractions also showed some degree of inhibition. In vivo tests revealed that the bacterium could induce growth promotion in tea varieties as determined by increase in plant height, number of branches and number of leaves. The bacterium could also reduce root rot of tea caused by Poria hypobrunnea. Enhanced accumulation of phenolics and activities of defense enzymes- peroxidase, phenyl alanine ammonia lyase, Î²1,3 glucanase and chitinase revealed the activation of systemic acquired resistance (SAR) in tea plants. HPLC analysis of catechins-the flavonoid flavor compounds of tea revealed the appearance of new isomers. Sustainability of the applied bacterium in the rhizosphere was detected by immunoassays. It is apparent from the results that B. pumilus has an array of mechanisms by which it induces plant growth promotion in tea.